INTEGRATION OF IOT AND GIS FOR OPTIMIZING DISASTER RELIEF DISTRIBUTION RESPONSE IN REMOTE AREAS - Syams Kurniawan Hidayat, (Journal of Computer Science and Technology (JCS-TECH), 2025)
Natural disasters often pose significant challenges in aid distribution, especially in remote areas with limited infrastructure and difficult access. Slow and inefficient responses can exacerbate the impact of disasters and lead to greater losses. This research proposes an integrated Internet of Things (IoT) and Geographic Information System (GIS) to optimize disaster aid distribution response in remote areas. The system is designed to provide real-time monitoring of logistics assets, efficient route planning, dynamic data management, and performance reporting. By leveraging IoT sensors for real-time field data collection and GIS spatial analysis capabilities for visualization and optimization, this system aims to enhance situational awareness, accelerate response times, and ensure aid reaches those in need more effectively and safely. Key features of the system include secure user authentication, an interactive real-time map dashboard, intelligent logistics route planning, dynamic data management, centralized IoT sensor monitoring, and performance reporting and analysis. This integration is expected to overcome various logistical constraints faced in disaster relief operations in challenging environments.